Application of Kahoot-Based Digital Assessments in Basic Physics Lectures: The Case of Muhammadiyah Makassar University - Nurlina, Nurlina; Marisda, Dewi Hikmah; Nurfadilah, Nurfadilah (FKIP Universitas Lampung, 2023)
Previous research has developed digital assessments in basic physics courses. This study aims to measure the effectiveness of implementing Kahoot-based digital assessments in Basic Physics courses at a private university in Makassar. This research is a pre-experimental study with a pretest-posttest design in one experimental class. The research sample is a saturated sample with 13 students as respondents. This study tested three types of questions, namely quiz, true-false, and multiple choice. The results of the data analysis show that the mean value for the pretest is 54.46 and the posttest is 85.87. In addition, an increase (n-gain) value of 0.68 was obtained in the medium category. The n-gain percentage value is 68.06 which means the effectiveness of the instrument is in the fairly effective category. Testing the pretest and posttest scores for each type of question shows an increase in learning outcomes for the type of question being tested. The pretest and posttest results for the three types of questions are presented in the form of a frequency distribution graph. After obtaining data on the effectiveness of using the Kahoot-based digital basic physics assessment, it is further suggested to test the practicality of the Kahoot-based basic physics assessment developed.Keywords: Learning assessment, basic physics, Kahoot application.DOI: http://dx.doi.org/10.23960/jpmipa/v24i1.pp152-160